Development and Psychometric Verification of the «Educational Self-Efficacy of the Adult» Questionnaire - Galtseva, Tetiana (Psychological Prospects Journal, 2018)
The article presents the procedure of development and psychometric verification of the author’s questionnaire, which studies the level of educational self-efficacy of the adult and its structural components. In order to find out the internal structure of the questionnaire and check its correspondence with the constructed theoretical model of training self-efficacy, a factor analysis was used that allowed to differentiate five scales of the questionnaire with a sufficiently high level of reliability. The questionnaire consists of 32 statements. Scales are identified as «Confidence in Own Educational Ability», «Value-Semantic Attitude to Educational Activities», «Motivational-Targeted Orientation in Learning», «Responsibility for Education and Self-development», «Prognostic-Reflexive Ability to Learn». The total score is represented by the scale «Overall Indicator of Educational Self-efficacy». Test standards were developed for each scale.The statistically significant correlation relations between the educational self-efficacy of the adult and the motivation for success and fear of failure (a method by A. A. Rean) have been established. The correlation between the educational self-efficacy scales of the adult and the scales of the self-confidence self-test (V. G. Romek), the scale of the overall self-efficacy of the individual (R. Schwarzer, M. Jerusalem in the adaptation of V. G. Romekd. The highest indicators of connection between the «Prognostic-Reflexive Ability to Learn» and «Planning» scales, between the «Motivational-Targeted Orientation in Learning» and «Purposefulness» scales, between the «Value-Semantic Attitude to Educational Activities» and «Self-organization» scales, between the «Overall Indicator of Educational Self-efficacy» and «Overall Indicator of Self-organization» scales were established. Indicators of the educational self-efficacy scales at a minor statistical level correlate with the «Orientation to the Present» scale. The questionnaire has successfully passed a test for discriminatory power, test-retest reliability, internal consistency and constructive validity. The high criterial validity of the developed method is revealed.
Keywords: educational self-efficacy of the adult, questionnaire, validity, reliability, psychometry.